Identifying the oral microbiome of adolescents with and without dental fluorosis based on full-length 16S rRNA gene sequencing - Luo, Shanshan; Shao, Ruirui; Hong, Yue; Zhang, Ting; Zhou, Qingshuai; Zhou, Qian; Rao, Fengqing; Zhao, Xingxing; Dong, Yangting; Zhu, Ruiyu; Ling, Ping; Cui, Guzhen; et al. (Frontiers in Microbiology, 2024)
Dental fluorosis, resulting from long-term environmental exposure to fluoride, is prevalent among diverse populations worldwide. Severe fluorosis not only compromises the aesthetic appeal of teeth but also impairs their functionality. This study aims to investigate the oral microbiome in dental fluorosis and the health individuals of adolescents living in the endemic fluorosis area of Guizhou, China through full-length 16S rDNA sequencing. Fourty-six individuals meet the sampling criteria, and we divided these samples into the following groups: a healthy group (H=23) and a dental fluorosis group (F=23), and two subgroups of Miao ethnicity: a healthy Miao group (Hm=13) and a dental fluorosis Miao group (Fm=15). A total of 660,389 high-quality sequences were obtained, and 12,007 Amplicon Sequence Variants (ASVs) were identified, revealing significant variations in oral microbiome between Fm and Hm groups. The composition of oral microbiota was similar between the H and F groups. At the genus level, Pseudopropionibacterium and at the species level, Streptococcus oralis_subsp.dentisani_clade_058 were less abundant in group F than in group H (P < 0.05). Further analysis revealed that the abundance of Capnocytophaga gingivalis and Kingella denitrificans was significantly lower in Fm fluorosis patients than in the Hm group (P < 0.05). Based on the LEfSe analysis, the potential core biomarkers in the oral of Fm fluorosis patients were identified at different taxonomic levels, ranging from phylum to species. These include Gammaproteobacteria, Prevotella sp_HMT_304, Gemella sanguinis, and Gracilibacteria_(GN02). Network analysis revealed that the microbiota in the fluorosis group exhibited more complex interactions with each other than the healthy group. Notably, within the Hm group, the potential biomarkers Capnocytophaga gingivalis and Kingella denitrificans exhibited a positive correlation. Finally, we employed PICRUSt2 analysis to explore the abundance clustering of the top 30 functional units in each sample, and we found that the metabolic pathway compositions of the four groups were similar. In summary, our findings suggest that the microbial composition of plaque in Hm patients with dental fluorosis is significantly altered, and we identified the potential marker microorganisms that contribute to these changes.